High-strength particle reinforced aluminum-lithium-based alloy and preparation process and application thereof

Through mechanical stirring+ultrasonic stirring composite refining process and multi -level thermal treatment process, the problem of poor performance of granular reinforcement aluminum lithium -lithium -based alloy mechanical properties, significantly improved its tensile strength and extension rate, and improved strength and plastic toughness.

CN119351836APending Publication Date: 2025-01-24DALIAN UNIV OF TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411465290.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The mechanical properties of existing particle-reinforced aluminum-lithium-based alloys are poor, especially during the smelting process, TiB2 particles are prone to precipitation to form clusters, destroying the mechanical properties of the alloy.

Method used

Refine the TIB2 particles distribution by mechanical stirring+ultrasonic mixing composite refining process, combined with two levels of uniform heat treatment, squeezing or rolling, solid solution, pre -stretching, and timeliness processing process to improve the mechanical performance of alloy.

Benefits of technology

A significant improvement of the tensile strength, yield strength and extension rate of high-strength particles enhanced aluminum lithium-lithium conformity alloy, reaching the tensile strength of 640-680MPa and an extension rate of 6.0-10.0%, improved its strength, plastic toughness and thermal processing performance Essence

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119351836A_ABST
    Figure CN119351836A_ABST
Patent Text Reader

Abstract

The invention provides a high-strength particle reinforced aluminum-lithium-based alloy as well as a preparation process and application thereof. The alloy comprises the following components in percentage by mass: 3.3 to 4.5 percent of Cu, 0.2 to 0.7 percent of Mg, 0.8 to 1.6 percent of Li, 0.2 to 0.8 percent of Ag, 0.2 to 0.6 percent of Mn, 0.01 to 0.2 percent of Zr, 0.2 to 0.6 percent of Zn, 0.1 to 0.8 percent of TiB2 and the balance of Al and inevitable impurity elements. The mass content of Ti is smaller than or equal to 0.15%, the mass content of Si is smaller than or equal to 0.1%, and the mass content of Fe is smaller than or equal The preparation of the aluminum-lithium alloy is realized through a method of combining a mechanical stirring and ultrasonic stirring composite refining process, extrusion / rolling and heat treatment, and the problem of performance reduction caused by TiB2 particle aggregation of the particle-reinforced aluminum-lithium-based alloy is effectively solved, so that the strength of the particle-reinforced aluminum-lithium-based alloy is improved, and the application range of the particle-reinforced aluminum-lithium-based alloy is expanded.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to alloy technology, and in particular to a high-strength particle-reinforced aluminum-lithium based alloy, and a preparation process and application thereof. Background Art

[0002] Aluminum-lithium alloy has the advantages of low density, high specific strength and specific stiffness, fatigue resistance and corrosion resistance. Replacing traditional aluminum alloy components with it can reduce the weight of the structure by 10% to 20% and increase the stiffness by 10% to 20%. It has broad application prospects in the fields of aerospace, national defense and transportation. There are many precipitates in aluminum-lithium alloy. The type, quantity, size and distribution of the precipitates determine the mechanical properties of aluminum-lithium alloy. Therefore, the study of the regulation and change of the precipitates and their influence on the mechanical properties of the materials has always been an important direction for the development of new aluminum-lithium alloy materials.

[0003] In the particle-enhanced aluminum-lithium based alloy of the present invention, TiB 2 The size and distribution of the particles can be regulated to further enhance the strengthening effect of the precipitated phase and improve the mechanical properties of the alloy. Generally speaking, the mechanical properties of particle-reinforced aluminum-lithium based alloys are greatly affected by the distribution of the particles. 2 The particle density is usually large, and it is more likely to precipitate, forming coarse clusters at the bottom. In addition, during the solidification process, the particles are easily pushed to the grain boundary by the solid-liquid interface front, forming a coarse second phase at the grain boundary, which destroys the mechanical properties of the alloy. Good ingot quality is the prerequisite for obtaining high-quality aluminum-lithium alloy. Therefore, during the aluminum-lithium alloy casting process, the homogenization of the melt during solidification and the subsequent microstructure formed greatly affect the subsequent process and the comprehensive performance of the final product. Summary of the invention

[0004] The purpose of the present invention is to propose a high-strength particle-reinforced aluminum-lithium based alloy to address the problem of poor mechanical properties of existing particle-reinforced aluminum-lithium based alloys. The alloy has good mechanical properties and has excellent strength, plasticity, toughness, hot working performance and anisotropy.

[0005] It should be noted that, in the present invention, unless otherwise specified, the specific meaning of "including" in relation to composition limitations and descriptions includes both open-ended "including", "comprising", etc. and similar meanings, as well as closed-ended "composed of", "composed of", etc. and similar meanings.

[0006] To achieve the above object, the technical solution adopted by the present invention is: a high-strength particle-reinforced aluminum-lithium based alloy, comprising the following components and their mass percentages: Cu: 3.3-4.5%, Mg: 0.2-0.7%, Li: 0.8-1.6%, Ag: 0.2-0.8%, Mn: 0.2-0.6%, Zr: 0.01-0.2%, Zn: 0.2-0.6%, TiB 2 : 0.1%~0.8%, the rest are Al and unavoidable impurity elements; the content of each impurity element is: Ti: ≤0.15%, Si: ≤0.1%, Fe: ≤0.1%.

[0007] Furthermore, the components and their mass percentages in the particle-enhanced aluminum-lithium based alloy are: Cu: 3.5-4.2%, Mg: 0.3-0.7%, Li: 1.0-1.4%, Ag: 0.3-0.8%, Mn: 0.3-0.5%, Zr: 0.01-0.15%, Zn: 0.3-0.6%, TiB 2 : 0.1%~0.6%, the rest are Al and unavoidable impurity elements; the content of each impurity element is, Ti: ≤0.15%, Si: ≤0.1%, Fe: ≤0.1%.

[0008] Furthermore, the high-strength particle-reinforced aluminum-lithium based alloy has a tensile strength of 640-680 MPa, a yield strength of 600-640 MPa, and an elongation of 6.0-10.0%.

[0009] Another object of the present invention is to disclose a preparation process of a high-strength particle-reinforced aluminum-lithium based alloy, which effectively solves the problem of TiB 2 The problem of particle cluster segregation is solved by further improving its mechanical properties and expanding its application scenarios through composition design and deformation heat treatment process. Specifically, the preparation process of the high-strength particle-reinforced aluminum-lithium based alloy includes the following steps:

[0010] (1) Vacuum melting and casting: The ingredients are prepared according to the mass percentage of each component of the alloy, the vacuum melting furnace is evacuated to below 100 Pa, and the temperature is increased to melt the raw materials;

[0011] (2) Stirring refining and casting: Stirring refining adopts a mechanical stirring + ultrasonic stirring composite refining process. The melt is first mechanically stirred for 2-10 minutes, then ultrasonically stirred for 2-10 minutes, and then cast into a mold to obtain an alloy ingot;

[0012] (3) Homogenization treatment: homogenize the alloy ingot at 400-520°C for 6-50h, and then water cool or air cool to room temperature after homogenization treatment;

[0013] (4) Extrusion: The alloy ingot is heated to 400-450°C, kept at this temperature for 2-12 hours, and then extruded at this temperature to obtain alloy rods;

[0014] Or, rolling: heating the alloy ingot to 400-450°C, keeping the temperature for 2-12 hours, and then rolling at this temperature to obtain the alloy plate;

[0015] (5) Solution treatment: Heat the alloy bars or plates in a furnace to 500-520°C, keep the temperature for 1-3 hours after the furnace temperature stabilizes, and quench with water to room temperature;

[0016] (6) Pre-stretching treatment: The alloy rod or alloy plate after solid solution is pre-stretched at room temperature with a deformation of 1 to 5%;

[0017] (7) Aging treatment: The pre-stretched alloy rod or alloy plate is heated to 150-190°C in a furnace, kept at a temperature of 16-32 hours after the furnace temperature stabilizes, and then water-cooled or air-cooled to room temperature to prepare a high-strength particle-reinforced aluminum-lithium based alloy.

[0018] Furthermore, in the vacuum casting of step (1), after the alloy raw materials are prepared, the pressure is evacuated to below 100 Pa, 1000-3000 Pa of argon gas is filled in, and the temperature is raised to no more than 850° C. to melt the raw materials.

[0019] Further, in step (2), the melt in step (1) is kept warm for 0.5-1h, and then mechanically stirred for 5-20min, and then ultrasonically stirred for 5-20min, the mechanical stirring parameter is 100-300r / min, and the ultrasonic stirring parameter is a frequency of 10-20kHz;

[0020] Furthermore, the homogenization process in step (3) is a two-stage homogenization process, and the specific steps are as follows:

[0021] a. Primary homogenization treatment: heating the aluminum-lithium alloy ingot obtained by vacuum casting at room temperature; when the temperature reaches 400-450°C, starting the first stage homogenization treatment, keeping the temperature for 6-18 hours;

[0022] b. Secondary homogenization treatment: After the first-stage homogenization treatment is completed, the temperature is raised to 460-520°C, and the second-stage homogenization treatment is started, and the temperature is kept for 16-32 hours;

[0023] Furthermore, in step (4), the extrusion ratio is 15 to 30:1, and the extrusion speed at the outlet is 1 to 6 m / min.

[0024] Furthermore, during the rolling in step (4), the deformation amount of a single pass is 20-30%, the total deformation amount is 80-95%, and the rolling time is 3-5 minutes.

[0025] Furthermore, in step (5), the quenching transfer time is controlled within 15 s.

[0026] Furthermore, in step (6), the alloy rod or alloy plate after solid solution is subjected to room temperature pre-stretching treatment, with a deformation amount of 1 to 5% and an intermediate interval time of less than 2 hours.

[0027] Furthermore, in step (7), the pre-stretched alloy rod or alloy plate is heated in a furnace to 160-180° C., kept warm for 18-28 hours after the furnace temperature stabilizes, and finally air-cooled to room temperature to prepare a high-strength particle-reinforced aluminum-lithium based alloy.

[0028] The above method prepares a high-strength particle-reinforced aluminum-lithium based alloy through mechanical stirring + ultrasonic stirring composite refining, homogenization treatment, extrusion, solid solution, pre-stretching, aging treatment and other process methods.

[0029] Another object of the present invention is to disclose a use of a high-strength particle-reinforced aluminum-lithium based alloy in the aerospace field.

[0030] The high-strength particle-reinforced aluminum-lithium based alloy of the present invention, its preparation process and use have the following advantages compared with the prior art:

[0031] 1) The preparation process of the high-strength particle-reinforced aluminum-lithium alloy of the present invention is to add TiB 2 The particles are then refined by mechanical stirring + ultrasonic stirring composite refining process to make TiB 2 The particle clusters are broken and diffused under the drive of ultrasonic cavitation bubble explosion, which increases the probability of particles being engulfed and dispersed, greatly refines the cast grain structure, and the fine grains give the aluminum-lithium alloy higher mechanical properties.

[0032] 2) In order to eliminate the influence of alloy element segregation on the subsequent processing performance of the alloy, the particle-reinforced aluminum-lithium-based alloy of the present invention is subjected to a two-stage homogenization heat treatment before thermal deformation. The mechanical stirring + ultrasonic stirring composite refining process and the two-stage heat treatment process greatly improve the structural segregation during the solidification process, which can better eliminate the copper-rich phase at the grain boundary, solve the problem of uneven chemical composition inside the grain, and improve the strength, plasticity, toughness, hot processing performance and anisotropy of the alloy product. The high-strength particle-reinforced aluminum-lithium-based alloy of the present invention has a tensile strength of 640-680MPa, a yield strength of 600-640MPa, and an elongation of 6.0-10.0%.

[0033] 3) The present invention uses extrusion or rolling to disperse the TiB dispersed inside and outside the grains during the deformation process. 2The synergistic effect of particles has a greater inhibitory effect on dislocation movement, and the dislocation density of the matrix is ​​significantly increased. On the one hand, it ensures the consistency of the deformation degree, and on the other hand, it provides enough dislocation density and nucleation points for the particle-reinforced aluminum-lithium based alloy, promoting the precipitation of strengthening phases during the aging process.

[0034] 4) The preparation method of the high-strength particle-reinforced aluminum-lithium-based alloy of the present invention can greatly refine the grains and improve the original fibrous structure on the basis of the traditional aluminum-lithium alloy preparation, thereby solving the problem of uneven organization and mechanical properties after deformation, and further improving the industrial application level of particle-reinforced aluminum-lithium-based alloy. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 The as-cast microstructure photos of the aluminum-lithium alloy of Example 1 and Comparative Example 1 of the present invention, wherein the left photo is the as-cast microstructure of Example 1, and the right photo is the as-cast microstructure of Comparative Example 1;

[0036] Figure 2 1 is the tensile stress-strain curve of the aluminum-lithium alloy of Example 1 of the present invention and Comparative Example 1;

[0037] Figure 3 The as-cast microstructure photos of the aluminum-lithium alloy of Example 2 and Comparative Example 2 of the present invention, wherein the left photo is the as-cast microstructure of Example 2, and the right photo is the as-cast microstructure of Comparative Example 2;

[0038] Figure 4 The tensile stress-strain curves of the aluminum-lithium alloys of Example 2 and Comparative Example 2 of the present invention;

[0039] Figure 5 The blank is prepared for the application example of the present invention. DETAILED DESCRIPTION

[0040] The present invention is further described below with reference to the examples. The description of the technical features described below is based on representative embodiments and specific examples of the present invention, but the present invention is not limited to these embodiments and specific examples. It should be noted that:

[0041] Unless otherwise stated, the units used in this specification are all international standard units, and the numerical values ​​and numerical ranges appearing in the present invention should be understood to include the inevitable systematic errors in industrial production.

[0042] In this specification, the numerical range expressed using "a numerical value A to a numerical value B" means a range including the endpoints numerical values ​​A and B.

[0043] In the present specification, a numerical range expressed using "above" or "below" means a numerical range including the number.

[0044] In this specification, the word "may" means both performing a certain process and not performing a certain process.

[0045] In this specification, the use of "optional" or "optional" indicates that certain substances, components, execution steps, application conditions and other factors are used or not used.

[0046] In this specification, when "normal temperature" or "room temperature" is used, the temperature may be 15-25°C.

[0047] In this manual, the reagents or instruments used without indicating the manufacturer are all conventional products that can be obtained through commercial purchase.

[0048] Example 1

[0049] This embodiment discloses a high-strength particle-enhanced aluminum-lithium-based alloy, which is prepared by obtaining a high-quality ingot through a mechanical stirring + ultrasonic stirring composite refining process, and then by a two-stage homogenization, extrusion, solid solution, pre-stretching, aging and other processes. The particle-enhanced aluminum-lithium-based alloy components are prepared according to the following mass percentages: Cu: 3.9%, Li: 1.1%, TiB 2 : 0.5%, Mg: 0.4%, Ag: 0.5%, Mn: 0.3%, Zn: 0.5%, Zr: 0.1%, the rest are Al and unavoidable impurity elements. The content of each impurity element is, Ti: ≤0.15%, Si: ≤0.1%, Fe: ≤0.1%.

[0050] The preparation process of the high-strength particle-reinforced aluminum-lithium based alloy comprises the following specific steps:

[0051] (1) Vacuum melting: All alloy elements are mixed according to weight percentage, and after drying, the mixed materials are loaded into the melting furnace, and then filled with 3000Pa argon gas, heated to 750℃ to melt the raw materials, and kept warm for 1h, and then mechanical stirring refining and ultrasonic stirring refining are carried out in turn. The time of both stirring refining is 10min to ensure that TiB 2 The particles are dispersed and after refining, the melt is poured into the mold to obtain a high-quality ingot. After testing, it is confirmed that there are no obvious shrinkage defects. The microstructure of the ingot is as follows Figure 1 shown.

[0052] (2) Primary homogenization treatment: the aluminum-lithium alloy ingot obtained in step (1) is placed in a heat treatment furnace equipped with multiple thermocouples, and heated to a temperature T1 of 450° C. in the furnace. After the temperature of each thermocouple reaches 450° C., the first-stage homogenization treatment time is started. The first-stage homogenization treatment time is 12 h.

[0053] (3) Secondary homogenization treatment: After the first-level homogenization treatment is completed, the heat treatment furnace is heated to T2 temperature 510°C. After the thermocouple temperatures at various locations in the heat treatment furnace are stable and the same as the furnace display temperature, the second-level homogenization and insulation timing is started. The second-level homogenization treatment time is 24 hours, and after completion, it is water-cooled to room temperature;

[0054] (4) Extrusion: placing the ingot obtained in step (3) in a heating furnace and heating it to 420° C., keeping the temperature for 2 h after the furnace temperature stabilizes, and then extruding at this temperature, with an extrusion ratio of 19:1 and an extrusion speed of 2 m / min at the outlet to obtain a rod with a diameter of Φ20 mm;

[0055] (5) Solution treatment: The rod obtained in step (4) is heated to 520°C in a furnace. When the temperature of the thermocouple and the furnace display is consistent, the holding timer is started. After holding for 2 hours, the rod is taken out and water-cooled to room temperature. The quenching transfer time is less than 15 seconds.

[0056] (6) Pre-stretching: The bar after solution treatment in step (4) is subjected to cold deformation treatment at room temperature with a deformation amount of 4%. After deformation, the bar is kept under loading for 30 seconds;

[0057] (7) Aging: The cold-deformed bar is heated to 175°C, and the temperature is kept constant for 18 hours after the thermocouple in the furnace and the furnace display temperature are consistent. Then, it is air-cooled to room temperature to obtain a high-strength particle-reinforced aluminum-lithium based alloy. The final mechanical properties are as follows: Figure 2 shown.

[0058] During the melting and casting process, thermocouples are placed inside and outside the crucible to ensure accurate temperature control. Thermocouples are placed inside the furnace and at the furnace door to avoid accidents caused by overheating of the melting and casting furnace.

[0059] The heating furnace used in the above heat treatment process is a muffle furnace with a heating rate of 10°C / min and a temperature control accuracy of ±2°C. The temperature control can be made more accurate through the control of multiple thermocouples, which can effectively improve the mechanical properties of the aluminum-lithium alloy.

[0060] Comparative Example 1

[0061] Comparative Example 1 provides a method of 2 The particle-enhanced aluminum-lithium alloy is obtained by a mechanical stirring + ultrasonic stirring composite refining process to obtain a high-quality ingot, and then prepared by two-stage homogenization, extrusion, solid solution, pre-stretching, aging and other processes. Among them, the particle-enhanced aluminum-lithium based alloy components are prepared according to the following mass percentages: Cu: 3.9%, Li: 1.1%, Mg: 0.4%, Ag: 0.5%, Mn: 0.3%, Zn: 0.5%, Zr: 0.1%, and the rest are Al and unavoidable impurity elements, and the content of each impurity element is Ti: ≤0.15%, Si: ≤0.1%, Fe: ≤0.1%.

[0062] The process of Comparative Example 1 is the same as that of Example 1 except for the alloy element composition.

[0063] During the melting and casting process, thermocouples are placed inside and outside the crucible to ensure accurate temperature control. Thermocouples are placed inside the furnace and at the furnace door to avoid accidents caused by overheating of the melting and casting furnace.

[0064] The heating furnace used in the above heat treatment process is a muffle furnace with a heating rate of 10°C / min and a temperature control accuracy of ±2°C. The temperature control can be made more accurate through the control of multiple thermocouples, which can effectively improve the mechanical properties of the aluminum-lithium alloy.

[0065] Figure 1 The microstructures of the aluminum-lithium alloys in the embodiment 1 and the comparative example 1 are as shown in FIG. 2 After the particles were cast, the as-cast grain structure was significantly refined. The mechanical properties of the products of Example 1 and Comparative Example 1 are shown in the attached figure. Figure 2 As shown, the tensile strength of Example 1 can reach 672.4 MPa, the yield strength can reach 630.6 MPa, and the elongation is about 6.8%; the strength of Comparative Example 1 is 604.9 MPa, the yield strength is 562.2 MPa, and the elongation is about 7.8%.

[0066] Example 2

[0067] This embodiment discloses a high-strength particle-enhanced aluminum-lithium-based alloy, which is prepared by obtaining high-quality ingots through a mechanical stirring + ultrasonic stirring composite refining process, and then by two-stage homogenization, rolling, solutionizing, pre-stretching, aging and other processes. The particle-enhanced aluminum-lithium-based alloy components are prepared according to the following mass percentages: Cu: 4.2%, Li: 1.1%, TiB 2 : 0.2%, Mg: 0.5%, Ag: 0.6%, Mn: 0.3%, Zn: 0.4%, Zr: 0.1%, the rest are Al and unavoidable impurity elements. The content of each impurity element is, Ti: ≤0.15%, Si: ≤0.1%, Fe: ≤0.1%.

[0068] The preparation process of the high-strength particle-reinforced aluminum-lithium based alloy comprises the following specific steps:

[0069] (1) Vacuum melting: All alloy elements are mixed according to weight percentage, and after drying, the mixed materials are loaded into the melting furnace, and then filled with 3000Pa argon gas, heated to 750℃ to melt the raw materials, and kept warm for 1h, and then mechanical stirring refining and ultrasonic stirring refining are carried out in turn. The time of both stirring refining is 10min to ensure that TiB 2 The particles are dispersed and after refining, the melt is poured into the mold to obtain a high-quality ingot. After testing, it is confirmed that there are no obvious shrinkage defects. The microstructure of the ingot is as follows Figure 3 As shown;

[0070] (2) Primary homogenization treatment: the aluminum-lithium alloy ingot obtained in step (1) is placed in a heat treatment furnace equipped with multiple thermocouples, and heated to a temperature T1 of 450° C. in the furnace. After the temperature of each thermocouple reaches 450° C., the first-stage homogenization treatment time is started. The first-stage homogenization treatment time is 12 h.

[0071] (3) Secondary homogenization treatment: After the first-level homogenization treatment is completed, the heat treatment furnace is heated to T2 temperature 510°C. After the thermocouple temperatures at various locations in the heat treatment furnace are stable and the same as the furnace display temperature, the second-level homogenization temperature holding timer is started. The second-level homogenization treatment time is 24 hours, and after completion, the treatment is cooled to room temperature with water.

[0072] (4) rolling: placing the ingot obtained in step (3) in a heating furnace and heating it to 420° C., keeping the temperature for 8 h after the furnace temperature stabilizes, and then rolling at this temperature, with the deformation of a single pass controlled at 20%, the total deformation of rolling controlled at 90%, and the rolling time being 5 min, to obtain a plate with a specification of 2*60*500 mm;

[0073] (5) Solution treatment: The plate obtained in step (4) is heated to 520°C in a furnace. When the temperature of the thermocouple and the furnace display is consistent, the heat preservation timer is started. After heat preservation for 2 hours, the plate is taken out and water-cooled to room temperature. The quenching transfer time is less than 15 seconds.

[0074] (6) Pre-stretching: the plate after solution treatment in step (5) is subjected to cold deformation treatment at room temperature, with a deformation amount of 4%, and maintained under loading force for 30 seconds after deformation;

[0075] (7) Aging: The cold-deformed bar is heated to 175°C, and the temperature is kept constant for 18 hours after the thermocouple in the furnace and the furnace display temperature are consistent. Then, it is air-cooled to room temperature to obtain a high-strength particle-reinforced aluminum-lithium based alloy. The final mechanical properties are as follows: Figure 4 As shown;

[0076] During the melting and casting process, thermocouples are placed inside and outside the crucible to ensure accurate temperature control. Thermocouples are placed inside the furnace and at the furnace door to avoid accidents caused by overheating of the melting and casting furnace.

[0077] The heating furnace used in the above heat treatment process is a muffle furnace with a heating rate of 10°C / min and a temperature control accuracy of ±2°C. The temperature control can be made more accurate through the control of multiple thermocouples, which can effectively improve the mechanical properties of the aluminum-lithium alloy.

[0078] Comparative Example 2

[0079] Comparative Example 2 provides a method of 2The production method of the aluminum-lithium alloy sheet of particles is to obtain high-quality ingots through mechanical stirring + ultrasonic stirring composite refining process, and then prepare them by two-stage homogenization, rolling, solid solution, pre-stretching, aging and other processes. Among them, the particle-enhanced aluminum-lithium based alloy components are prepared according to the following mass percentages: Cu: 4.2%, Li: 1.1%, Mg: 0.5%, Ag: 0.6%, Mn: 0.3%, Zn: 0.4%, Zr: 0.1%, and the rest are Al and unavoidable impurity elements, and the content of each impurity element is, Ti: ≤0.15%, Si: ≤0.1%, Fe: ≤0.1%.

[0080] Except for the alloying element composition, the production process of Comparative Example 1 is the same as that of Example 1.

[0081] During the melting and casting process, thermocouples are placed inside and outside the crucible to ensure accurate temperature control. Thermocouples are placed inside the furnace and at the furnace door to avoid accidents caused by overheating of the melting and casting furnace.

[0082] The heating furnace used in the above heat treatment process is a muffle furnace with a heating rate of 10°C / min and a temperature control accuracy of ±2°C. The temperature control can be made more accurate through the control of multiple thermocouples, which can effectively improve the mechanical properties of the aluminum-lithium alloy.

[0083] Figure 3 The microstructures of the aluminum-lithium alloys of Example 2 and Comparative Example 2 are as-cast. It can be seen that the addition of 0.02% TiB 2 After the particles are added, the as-cast grain structure does not change much. Figure 4 As shown, the mechanical properties of Example 2 are significantly improved, and its tensile strength can reach 652.1 MPa, yield strength can reach 613.7 MPa, and elongation can reach 7.0%; the tensile strength of Comparative Example 2 is 633.1 MPa, the yield strength is 572.1 MPa, and the elongation is 6.1%; compared with Comparative Example 2, the strength and elongation of Example 2 are increased to a certain extent.

[0084] Application Example 1

[0085] Compared with ordinary aluminum-lithium alloys, the high-strength particle-reinforced aluminum-lithium based alloy of the present invention has higher elastic modulus and specific strength. In the field of aerospace, it can replace 2219 and 7050 aluminum alloys to make certain precision parts. Figure 5 Using this material to make corresponding parts can reduce the weight of the component by about 10-20%, improve the mechanical properties, and effectively reduce the deformation of the workpiece, which has a good application prospect.

[0086] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A high-strength particle-reinforced aluminum-lithium based alloy, characterized in that: The components and their mass percentage are: Cu: 3.3-4.5%, Mg: 0.2-0.7%, Li: 0.8-1.6%, Ag: 0.2-0.8%, Mn: 0.2-0.6%, Zr: 0.01-0.2%, Zn: 0.2-0.6%, TiB2: 0.1-0.8%, and the rest are Al and unavoidable impurity elements; the content of each impurity element is: Ti: ≤0.15%, Si: ≤0.1%, Fe: ≤0.1%.

2. A process for preparing the high-strength particle-reinforced aluminum-lithium based alloy according to claim 1, characterized in that: The following steps are involved: (1) Vacuum melting and casting: The ingredients are prepared according to the mass percentage of each component of the alloy, the vacuum melting furnace is evacuated to below 100 Pa, and the temperature is increased to melt the raw materials; (2) Stirring refining and casting: Stirring refining adopts a mechanical stirring + ultrasonic stirring composite refining process. The melt is first mechanically stirred for 2-10 minutes, then ultrasonically stirred for 2-10 minutes, and then cast into a mold to obtain an alloy ingot; (3) Homogenization treatment: homogenize the alloy ingot at 400-520°C for 6-50h, and then water cool or air cool to room temperature after homogenization treatment; (4) Extrusion: The alloy ingot is heated to 400-450°C, kept at this temperature for 2-12 hours, and then extruded at this temperature to obtain alloy rods; Or, rolling: heating the alloy ingot to 400-450°C, keeping the temperature for 2-12 hours, and then rolling at this temperature to obtain the alloy plate; (5) Solution treatment: Heat the alloy bars or plates in a furnace to 500-520°C, keep the temperature for 1-3 hours after the furnace temperature stabilizes, and quench with water to room temperature; (6) Pre-stretching treatment: The alloy rod or alloy plate after solid solution is pre-stretched at room temperature with a deformation of 1 to 5%; (7) Aging treatment: The pre-stretched alloy rod or alloy plate is heated to 150-190°C in a furnace, kept at a temperature of 16-32 hours after the furnace temperature stabilizes, and then water-cooled or air-cooled to room temperature to prepare a high-strength particle-reinforced aluminum-lithium based alloy.

3. The preparation process of the high-strength particle-reinforced aluminum-lithium based alloy according to claim 2, characterized in that: The vacuum melting and casting in step (1) is as follows: after the alloy raw materials are prepared, the pressure is evacuated to below 100 Pa, 1000-3000 Pa of argon gas is filled in, and the temperature is raised to no more than 850° C. to melt the raw materials.

4. The preparation process of the high-strength particle-reinforced aluminum-lithium based alloy according to claim 2, characterized in that: Step (2) The melt in step (1) is kept warm for 0.5-1h, and then mechanically stirred for 5-20min, and then ultrasonically stirred for 5-20min, wherein the parameters of mechanical stirring are 100-300r / min, and the parameters of ultrasonic stirring are frequency 10-20kHz.

5. The preparation process of the high-strength particle-reinforced aluminum-lithium based alloy according to claim 2, characterized in that: The homogenization process in step (3) is a two-stage homogenization process, and the specific steps are as follows: a. Primary homogenization treatment: heating the aluminum-lithium alloy ingot obtained by vacuum casting at room temperature; when the temperature reaches 400-450°C, starting the first stage homogenization treatment, keeping the temperature for 6-18 hours; b. Secondary homogenization treatment: After the first-level homogenization treatment is completed, the temperature is raised to 460-520°C, and the second-level homogenization treatment is started, and the temperature is kept for 16-32 hours.

6. The preparation process of the high-strength particle-reinforced aluminum-lithium based alloy according to claim 2, characterized in that: The extrusion ratio of step (4) is 15 to 30:1, and the extrusion speed at the outlet is 1 to 6 m / min.

7. The process for preparing the high-strength particle-reinforced aluminum-lithium based alloy according to claim 2, characterized in that: During the rolling in step (4), the deformation amount of a single pass is 20-30%, the total deformation amount is 80-95%, and the rolling time is 3-5 minutes.

8. The process for preparing the high-strength particle-reinforced aluminum-lithium based alloy according to claim 2, characterized in that: In step (5), the quenching transfer time is controlled within 15 s.

9. The process for preparing the high-strength particle-reinforced aluminum-lithium based alloy according to claim 2, characterized in that: In step (6), the alloy rod or alloy plate after solid solution is subjected to room temperature pre-stretching treatment, with a deformation amount of 1 to 5% and an intermediate interval time of less than 2 hours.

10. Use of the high-strength particle-reinforced aluminum-lithium based alloy according to claim 1 in the field of aerospace.

Citation Information

Cited By

  • Aluminum-lithium alloy and preparation method thereof

    CN119956174A